KOHERENSI ANTARA HUKUM JINAYAT DAN HAK ASASI MANUSIA DALAM KASUS KHAMAR DI ACEH - Maha, Esa; Alief, Vania; Ash Shabah, Musyaffa Amin (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2023)
Public flogging is required by this jinayat law, which has existed since 2014. It is thought to be a severe and effective method of law enforcement. But there have also been a lot of complaints and criticisms of this jinayat law, particularly from the standpoint of human rights. The local community's justice, welfare, and peace are the main goals of Aceh's implementation of jinayat law. In the paper utilized for this study, the author employs normative juridical research, which is legal research done by looking through books and relevant statutes and regulations from libraries. This research employs a qualitative approach using a library research method by the study's characteristics. This research also employs a comparative methodology; specifically, the author compares Islamic law, human rights, and the Aceh Qanun Jinayat. As per the Aceh Qanun Jinayat and Islamic law, there is a whipping law for anyone who consumes alcohol. This is evident from the punishment meted out to the alcohol user, who is flogged 40 (forty) times as Uqubat Hudud. Acehnese people have lived under Islamic law for a long time, earning them the moniker "land of the porch of Makkah." When non-Muslim suspects of violating the qanun voluntarily turn themselves in for punishment, it is evident that Islamic Sharia's conceptions of justice align with the fundamental principles of legal justice and human rights. The courts denied every request for voluntary surrender made by non-Muslim defendants, although they did acknowledge the primary motivators behind their surrender.